2020
DOI: 10.1038/s41467-020-18074-8
|View full text |Cite
|
Sign up to set email alerts
|

Interneuron-specific plasticity at parvalbumin and somatostatin inhibitory synapses onto CA1 pyramidal neurons shapes hippocampal output

Abstract: The formation and maintenance of spatial representations within hippocampal cell assemblies is strongly dictated by patterns of inhibition from diverse interneuron populations. Although it is known that inhibitory synaptic strength is malleable, induction of long-term plasticity at distinct inhibitory synapses and its regulation of hippocampal network activity is not well understood. Here, we show that inhibitory synapses from parvalbumin and somatostatin expressing interneurons undergo long-term depression an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
110
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 79 publications
11
110
0
Order By: Relevance
“…Diet-associated reductions of PV neuron immunoreactivity and PNNs were observed within the CA1 of the adult cohort, suggesting that this region may be more vulnerable to nutritional stress. This aligns with previous observations of pronounced obesity-induced cognitive deficits in spatial memory 14 , 15 , 63 , 64 , as PV-mediated inhibitory neurotransmission within the CA1 is required for the stabilisation of place cells 65 . The most prominent diet-evoked changes to PV neurons and PNNs were observed in the adult cohort, supported further by negative associations between adiposity and numbers of PNNs within the CA1 and CA2/3 in the adult cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Diet-associated reductions of PV neuron immunoreactivity and PNNs were observed within the CA1 of the adult cohort, suggesting that this region may be more vulnerable to nutritional stress. This aligns with previous observations of pronounced obesity-induced cognitive deficits in spatial memory 14 , 15 , 63 , 64 , as PV-mediated inhibitory neurotransmission within the CA1 is required for the stabilisation of place cells 65 . The most prominent diet-evoked changes to PV neurons and PNNs were observed in the adult cohort, supported further by negative associations between adiposity and numbers of PNNs within the CA1 and CA2/3 in the adult cohort.…”
Section: Discussionsupporting
confidence: 92%
“…These roles are remarkably similar to those identified for PV + and SST + interneurons in CA1, where PV + interneurons regulate CA3 drive and SST + interneurons regulate EC drive (FernĂĄndez-Ruiz et al, 2017;Udakis et al, 2020). We therefore hypothesize that across the hippocampus, PV + and SST + interneurons are likely to be modulated coherently as different flows of information are needed.…”
Section: Discussionsupporting
confidence: 64%
“…In CA1, these cells receive primarily local inputs from pyramidal cells and thus provide feedback inhibition (Freund and BuzsĂĄki, 1998;Wheeler et al, 2015). Consistent with these patterns of inputs, potentiation of PV + interneurons attenuates CA3 inputs while potentiation of CA1 SST + interneurons attenuates EC inputs (FernĂĄndez-Ruiz et al, 2017;Udakis et al, 2020).…”
Section: Introductionmentioning
confidence: 75%
“…At the cellular level, animal studies have now shown that, tight regulation of cortical excitability is governed by an interplay between excitatory and inhibitory neurons and that disruption of this balance can lead to epileptic seizures 25 . In particular, GABAergic inhibition plays a key role in regulating cortical excitability 26–28 as well as seizure likelihood 29 , threshold 24 , duration 30 and severity 31 . Further, GABAergic transmission can be measured using single and paired pulse protocols as evoked cortical responses change in presence of GABA A agonist 17,19,32–34…”
Section: Introductionmentioning
confidence: 99%